THE CORRELATION OF STUDENTS PERCEPTIONS OF THE LEARNING ENVIRONMENT WITH SCIENCE LEARNING OUTCOMES AT MTS NEGERI 1 PASURUAN - Rahma, Azizatur; Shofiyah, Noly (PT. Antis International Publisher, 2025)
Objective: The purpose of this study was to describe the correlation between students' perceptions of the learning environment and science learning outcomes at MTs Negeri 1 Pasuruan. Method: Non-experimental quantitative research method with correlational research type. The population of this study were students in grades VII, VIII, and XI, the research sample numbered 96 people. Results: The relationship (correlation) between students' perceptions of the science learning environment and students' science learning outcomes, obtained a significant result of 0.95 <0.05 so that it shows that there is a positive correlation between the perception of the learning environment and the learning outcomes of students. The conclusion of this study is that there is a correlation between variables X and Y classified as very strong in the correlation test interpretation table. Novelty: This study highlights a very strong correlation between students' perceptions of the science learning environment and their science learning outcomes, providing empirical support for the importance of perception in educational success, specifically in the context of MTs Negeri 1 Pasuruan.